Biochemical and clinical predictors of hypoxic–ischemic encephalopathy after perinatal asphyxia. (19th March 2018) - Jones, Rebekka; Heep, Axel; Odd, David
Abstract: Objective: To determine the usefulness of measures, available shortly after birth, as predictors of hypoxic–ischemic encephalopathy (HIE) following perinatal asphyxia. Patients: All inborn patients at Southmead Hospital between January 2012 and March 2014 at ≥36 weeks gestation with a pH <7 or BE >16 on cord or baby's blood within one hour of birth or 10-minute Apgar score ≤5 or requiring intermittent positive pressure ventilation at 10 minutes were eligible for inclusion. Methods: ROC curves were derived for the perinatal clinical and biochemical measures to establish their predictive values for the development of HIE and the area under the curve (AUC) used as the measure of prediction. Results: We identified 79 eligible babies. Infants qualifying for therapeutic hypothermia (TH) based on aEEG abnormalities were considered to have HIE ( n  = 13; 16.5%), whereas babies with normal aEEG were classified as "non-HIE" ( n  = 66; 83.5%). The highest AUC measure was associated with the five-minute Apgar score (0.89 (0.79–0.99)). Troponin T (0.81 (0.64–0.98)) and ALT (0.78 (0.60–96)) also showed high values. Conclusions: In this work, the Apgar score, troponin T and ALT were found to be strong and useful predictors of HIE.